Alcohol consumption and atrial fibrillation risk: An updated dose-response meta-analysis of over 10 million participants - Jiang, Hezi; Mei, Xiaofei; Jiang, Yufeng; Yao, Jialu; Shen, Jinsheng; Chen, Tan; Zhou, Yafeng (Frontiers in Cardiovascular Medicine, 2022)
Background The treatment of atrial fibrillation (AF) has made significant progress, but the prevention of AF has not received the attention it deserves. A few recent large-sized studies have conducted dose response analysis and reported different conclusions from previous studies on alcohol consumption and AF risk. Objectives The aim of this study is to examine the potential non-linear association between alcohol consumption and risk of AF and explore the potential differences of gender. Methods In this updated dose-response meta-analysis, PubMed, Embase and Cochrane databases were searched until June 2022. Risk estimates were reported as relative risk (RR) with 95% confidence intervals (CIs). The random-effects restricted cubic spline models are used to evaluate the potential non-linear association between alcohol consumption and AF risk. Results A total of 10,151,366 participants with 214,365 cases of AF enrolled in 13 prospective studies. The overall meta-analysis showed that a 1 drink/day increase in alcohol consumption increased the risk of AF by 6% (RR: 1.06; 95% CI: 1.03–1.08). In gender subgroup analysis, pooled results were different between men (RR: 1.08; 95% CI: 1.05–1.11) and women (RR: 1.05; 95% CI: 0.96–1.14). A linear relationship between alcohol consumption and risk of AF was found in men (p = 0.87) while a J-shaped curve was observed in women (p = 0.00). Regional subgroup analysis yielded broadly comparable results in Americas (RR: 1.07; 95% CI: 1.03–1.12), Europe (RR: 1.04; 95% CI: 0.99–1.1) and Asia (RR: 1.07; 95% CI: 0.99–1.14). Conclusion The relationship between AF risk and alcohol consumption is linear in men, while a potential non-linear J-shaped relationship is shown in women. Condensed abstract We conducted a dose-response meta-analysis on the relationship between alcohol consumption and risk of atrial fibrillation. We merged the data of over 10 million participants and found gender differences in the pattern of association with AF and alcohol consumption. The relationship between AF risk and alcohol consumption is linear in men, while a potential non-linear J-shaped relationship is shown in women. In summary, this research is vital in furthering our understanding of the role of alcohol consumption in new-onset AF, especially among different genders.